PENGUKUHAN KAWASAN HUTAN LINDUNG GUNUNG BUKIT PANTI KABUPATEN TANAH LAUT PROVINSI KALIMANTAN SELATAN - Rahmad Effendi; Mufidah Asy'ari; Syam’ani Syam’ani (Universitas Lambung Mangkurat, 2020)
The purpose of this study was to find out about the inauguration of a mountain hill protected forest area and identify land cover in Tanah Laut Regency, South Kalimantan Province. The results of the study showed that the area of the protected mountainside of the panti hill had changed because at the time of the implementation of the boundary arrangement in the field there were rights of third parties in the form of settlements so that the area was excluded from the area. The attitude of the community around the forest area agrees and welcomes the existence of protected forest areas. Closure of land in the form of dry land agriculture mixed with bushes, plantations, oil palm, shrubs and rubber.Keywords: Boundaries; forest